2011
DOI: 10.1177/0959683611400463
|View full text |Cite
|
Sign up to set email alerts
|

Where were the northern elephant seals? Holocene archaeology and biogeography of Mirounga angustirostris

Abstract: Northern elephant seals (NES hereafter, Mirounga angustirostris) were nearly driven to extinction by commercial and recreational hunters during the nineteenth century fur and oil trade (Scammon, 1874: 119; Stewart et al., 1994). Despite limited genetic diversity (Bonnell and Selander, 1972; Weber et al., 2000, 2004), NES along North America's Pacific Coast are now thriving, with some 124 000 animals in the California stock alone (Carretta et al., 2009: 28). The recovery of NES populations is one of the success… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 38 publications
0
23
0
Order By: Relevance
“…Meta-analyses of archaeozoological data provide explanations of fine-grained questions using large databases (Conolly et al 2011;Cranbrook and Piper 2009;Emery 2007;Grayson and Meltzer 2002;Grayson 2005;Rick et al 2011). A classic example of a meta-analysis is the recognition that we only have evidence for Clovis-era hunter-gatherers in North America exploiting two of the 35 large mammal genera that became extinct during the late Pleistocene (Grayson and Meltzer 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Meta-analyses of archaeozoological data provide explanations of fine-grained questions using large databases (Conolly et al 2011;Cranbrook and Piper 2009;Emery 2007;Grayson and Meltzer 2002;Grayson 2005;Rick et al 2011). A classic example of a meta-analysis is the recognition that we only have evidence for Clovis-era hunter-gatherers in North America exploiting two of the 35 large mammal genera that became extinct during the late Pleistocene (Grayson and Meltzer 2002).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to the relative surplus of fur seals in the archaeological records, northern elephant seals are notably, and surprisingly, scarce relative to their contemporary abundance (Rick et al. ). It has been suggested that elephant seals were displaced early on from coastal sites to remote island settings by terrestrial predators (e.g., grizzly bears and mountain lions) and Native American settlements (Rick et al.…”
Section: Focal Speciesmentioning
confidence: 99%
“…It has been suggested that elephant seals were displaced early on from coastal sites to remote island settings by terrestrial predators (e.g., grizzly bears and mountain lions) and Native American settlements (Rick et al. ), with records of these early hunts lost to rising sea levels (Braje et al. ).…”
Section: Focal Speciesmentioning
confidence: 99%
“…As a variety of researchers have noted, harbor seals are among the more skittish and flightprone pinnipeds, making them more difficult to obtain and often less desirable than some higher-ranking otariids (see Hildebrandt and Jones, 1992;Braje et al, 2011). The presence of a single elephant seal bone each at CA-ANI-2 and CA-ANI-8 and their occurrence at CA-ANI-6 are interesting given how rare the remains of elephant seals are at Channel Island sites (Rick et al, 2011). Elephant seals require sandy beaches for hauling out, so on the basis of current shorelines, the island's only suitable habitat for them would be the fairly small beach at Frenchy's Cove on West Anacapa, which is near both CA-ANI-6 and CA-ANI-8.…”
Section: Historical Ecology Of Anacapa Islandmentioning
confidence: 99%